A study of motivation and team member selection in online games. Issue 6 (12th November 2019) - Lou, Tianyang; Zu, Yuning; Zhu, Ling
Abstract : Purpose: The purpose of this paper is to investigate impact of playing motivation on team member selection (TMS) in online games specifically related to Massively Multiplayer Online Role-playing Game environment. Design/methodology/approach: A self-administered questionnaire was developed and administered to an online sample of 9, 335 CR3 players. Findings: The findings of this research indicated that social and immersion motivations have a significant effect on TMS. Additionally, it was discovered that achievement motivation has a positive relationship with dispositional TMS, a negative relationship to bond-based TMS. The moderation effect of frequency and gender is also demonstrated. Research limitations/implications: The study verified the relationships of the theoretical model of the game motivation and TMS. Originality/value: This study provides advice to operators of online games when motivating players to work in groups.